2020
DOI: 10.1109/access.2020.3027710
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Operation of Local Energy Community Providing Frequency Restoration Reserve

Abstract: This work was undertaken as part of the FLEXIMAR project (novel marketplace for energy flexibility) with financial support provided by Business Finland (Grant No. 6988/31/2018) as well as Finnish companies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…A four-week simulation is performed adopting the IEEE European low voltage test feeder -solved via OpenDSS -and 44 consumers having a 4 kWp PV on the rooftop. Similarly, a two-stages stochastic method based on a Mixed-Integer Linear Programming (MILP) optimization model is used in [19] ] for the optimal operation of a local energy community to participate in providing manual frequency restoration reserve (mFRR). The case study consists of 50 households, distributed 100kW PV systems, a centralized 50 kW/200k Wh Vanadium Redox Flow battery, and 10 electric vehicles.…”
Section: A Related Workmentioning
confidence: 99%
“…A four-week simulation is performed adopting the IEEE European low voltage test feeder -solved via OpenDSS -and 44 consumers having a 4 kWp PV on the rooftop. Similarly, a two-stages stochastic method based on a Mixed-Integer Linear Programming (MILP) optimization model is used in [19] ] for the optimal operation of a local energy community to participate in providing manual frequency restoration reserve (mFRR). The case study consists of 50 households, distributed 100kW PV systems, a centralized 50 kW/200k Wh Vanadium Redox Flow battery, and 10 electric vehicles.…”
Section: A Related Workmentioning
confidence: 99%
“…Ref. [14] demonstrated that local energy communities connected to distribution networks could be potential resources for providing manual FRR services for TSOs. The authors of [15] analyzed the deployment of grid-connected PV (Photovoltaic) panels integrated with the battery energy storage system (BESS) to follow the TSO regulation signals.…”
Section: ) System-wide Flexibility Provisionmentioning
confidence: 99%
“…7). To develop the mathematical models of EVs and batteries, we utilize the [14] while for the electric heaters, the model is extracted from [43].…”
Section: Case Studymentioning
confidence: 99%
“…A promising way to deal with the energy management of prosumers is to gather individual prosumers into a group-wide system, and the energy community (EC) is one of the most typical concepts that has attracted much attention (Cai et al, 2017;Firoozi et al, 2020). The paper of Bera et al (2018) analyzes the formatting process of an EC from a dynamic perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Despite those comprehensive works, there still exist some gaps, which the current work seeks to fill. The previous literatures comprehensively analyze the structures and behaviors of ECs with only electricity carrier (Cai et al, 2017;Ye et al, 2017;Bera et al, 2018;Feng et al, 2020;Firoozi et al, 2020;Lilla et al, 2020;Cui et al, 2021), but barely focus on building a multi-energy community (MEC) with multi-energy interactions and analyzing the trading mechanism of it. In Ma et al (2019), an EH is proposed to interact different energy carriers in an EC, but it is viewed as an EC operator in the leading level, which means the EH is not on the same status as prosumers and can lead the transaction with prosumers.…”
Section: Introductionmentioning
confidence: 99%